Connection and happiness: an interactive study of social media, social capital, and the subjective well-being of international students - Duan, Ninggui; Lu, Hong; Lyu, Huihui (Frontiers in Psychology, 2025)
The subjective well-being of international students is crucial for their adaptation and academic success in a foreign country. Based on online social capital theory, this study examines how social media use affects the subjective well-being of international students and explores the underlying mechanisms and the moderating role of college attachment. A questionnaire survey was conducted among 21 universities in China, yielding 474 valid responses, which were analyzed using structural equation modeling. The findings indicate that social media use significantly and positively predicts the subjective well-being of international students, as well as bridging, bonding, and maintaining social capital. Notably, only bonding social capital partially mediates the relationship between social media use and subjective well-being. Additionally, college attachment positively moderates the indirect effect of bridging social capital only, but it did not significantly moderate the relationship between social media use and subjective well-being. These results highlight that social media use can enhance the subjective well-being of international students through social capital. This effect is moderated by college attachment, providing valuable insights for relevant stakeholders.